The Nautical Magazine for 1873 (Cambridge library collection. Nautical magazine, 1873)
The Nautical Magazine first appeared in 1832, and was published monthly well into the twenty-first century. It covers a wide range of subjects, including navigation, meteorology, technology and safety. An important resource for maritime historians, it also includes reports on military and scientific expeditions and on current affairs. The volume for 1873 continues the new policy of reporting on learned societies and legal matters. Technical aspects of iron ships, steam engines and lifeboats feature prominently, and scientific discussions cover the polar regions, the transit of Venus, and tsunamis. A series of articles describes 'our great ports', including Liverpool, Newcastle, Dublin and Southampton. However, the volume is dominated by an increasingly scathing editorial response to Samuel Plimsoll's proposed legislation against unseaworthiness and overloading, while Lloyds of London's new rule of freeboard is described as 'a dead imposition on shipowners and of no real benefit to the sailor'